Oxysterols in catfish skin secretions (Arius bilineatus, Val.) exhibit anti-cancer properties - Al-Hassan, Jassim M.; Afzal, Mohammad; Oommen, Sosamma; Liu, Yuan Fang; Pace-Asciak, Cecil (Frontiers in Pharmacology, 2022)
The edible catfish Arius bilineatus, (Valenciennes) elaborates a proteinaceous gel-like material through its epidermis when threatened or injured. Our on-going studies on this gel have shown it to be a complex mixture of several biologically active molecules. Anti-cancer studies on lipid fractions isolated from the gel-like materials showed them to be active against several cancer cell lines. This prompted us to investigate further the lipid composition of the catfish epidermal gel secretions (EGS). Analysis of the lipid fraction of EGS resulted in identification of 12 oxysterols including cholesterol and 2 deoxygenated steroids i.e. 7α-hydroxy cholesterol, 7-hydroxycholesterol, 5,6 epoxycholesterol, 3-hydroxycholest-5-ene-7-one and cholesta-3,5-dien-7-one. Progesterone, cholest-3,5-diene, cholesta-2,4-diene, cholest-3,5,6-triol and 4-cholesten-3-one were found as minor components, and were identified through their MS, 1HNMR and FTIR spectral data and were compared with those of the standards. Cholest-3,6-dione, cholesta-4,6-diene-3-one, cholesta-2,4-diene, and cholesta-5,20(22)-dien-3-ol were found only in trace amounts and were identified by GC/MS/MS spectral data. Since cholesterol is the major component of EGS, the identified oxysterols (OS) are presumably cholesterol oxidation products. Many of the identified OS are known important biological molecules that play vital physiological role in the producer and recipient organisms. We report herein the effects of these sterols on three human cancer cell lines in vitro, i.e. K-562 (CML cell line), MDA MB-231 (estrogen positive breast cancer cell line) and MCF-7 (estrogen negative breast cancer cell line). Interestingly significant (p<0.05) dose differences were observed between tested OS on cell types used. The presence of these sterols in EGS may help explain some aspects of the physiological activities of fraction B (FB) prepared from EGS, such as enhanced wound and diabetic ulcer healing, anti-inflammatory action and cytotoxic activities reported in our previous studies. The anti-proliferative actions of some of these oxysterols especially the cholesterol 3,5,6-triol (#5) as established on selected cancer cell lines in this study support our previous studies and make them candidates for research for human application.